Protocol for the site-specific isolation of mouse endothelial cells using the modified Häutchen technique - Alexander Brückner; Adrian Brandtner; Sarah Rieck; Bernd K. Fleischmann; Daniela Wenzel (STAR Protocols)
Summary: Endothelial cells (ECs) play a major role in vascular homeostasis and pathology. They show a pronounced heterogeneity between different organs as well as within the same organ. Here, we present a protocol for the rapid site-specific isolation of murine aortic ECs. We describe steps for vessel preparation and the isolation of EC layers by freezing on glass coverslips using a modified Häutchen technique. This protocol can be adapted to investigate surface cells from other tissues as well.For complete details on the use and execution of this protocol, please refer to Brückner et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.